Current physical activity and sports history of children 11 to 19 years old at high schools in Prague - Lukáš Babický; Tereza Nováková; Jan Vávra; Lenka Satrapová (Karolinum Press, 2020)
Objectives. Objective of this study/thesis/work was to analyse the level of free time physical activity and its specifics on a sample of the adolescent population. To goal was to analyze the historical factor in each proband and its effect on the activity development. The analysis included information spanning from the initial experience with organized physical activity. The results of the survey are further compared with the conclusions of previous studies on the issue. Methods. A total of 563 respondents (235 boys and 328 girls) from grammar schools in Prague participated in the research. Data were obtained using a questionnaire survey (computer assisted web interviewing - CAWI) based on preliminary research and evaluated using MS Excel, GraphPad Prism and mathematical software R. Results. The preference of just one sport (63.8%) was found in the examined population. Predominant frequency of trainings was 2 to 4 per week (61.2%). The vast majority (93.6%) stated that they participated in fundamental movement training at a younger school age. More than half (61%) experienced pain or injury during physical activity, especially in the lower limbs (61.9%). The main factor in the termination of physical activity were psychosocial reasons (76.9%). Increasing age has not been shown as a factor leading to reduction of physical activity in children. On the contrary, the frequency of activity increased as the children aged (p = 0.02). There was no significant dependence of the current activity on the completion of fundamental movement training (p = 0.08), nor was the confirmation of a general trend of higher activity of boys compared to girls (p = 0.64).